Apocynin attenuates testicular ischemia-reperfusion injury in rats - ŞİMŞEK, FERRUH; ERCAN, FERİHA; ŞENER, GÖKSEL; YÜKSEL, MERAL; ŞENER, TARIK EMRE (W B SAUNDERS CO-ELSEVIER INC, 2015)
Objective: This study was designed to examine the possible protective effect of apocynin, a NADPH oxidase inhibitor, against torsion/detorsion (T/D) induced ischemia/reperfusion (I/R) injury in testis. Methods: Male Wistar albino rats were divided into sham-operated control, and either vehicle, apocynin 20 mg/kg-or apocynin 50 mg/kg-treated T/D groups. In order to induce I/R injury, left testis was rotated 720 degrees clockwise for 4 hours (torsion) and then allowed reperfusion (detorsion) for 4 hours. Left orchiectomy was done for the measurement of tissue malondialdehyde (MDA), glutathione (GSH) levels, myeloperoxidase (MPO) activity, and luminol, lucigenin, nitric oxide (NO) and peroxynitrite chemiluminescences (CL). Testicular morphology was examined by light microscopy. Results: I/R caused significant increases in tissue luminol, lucigenin, nitric oxide and peroxynitrite CL demonstrating increased reactive oxygen and nitrogen metabolites. As a result of increased oxidative stress tissue MPO activity, MDA levels were increased and antioxidant GSH was decreased. On the other hand, apocynin treatment reversed all these biochemical indices, as well as histopathological alterations that were induced by I/R. According to data, although lower dose of apocynin tended to reverse the biochemical parameters, high dose of apocynin provides better protection since values were closer to the control levels. Conclusion: Findings of the present study suggest that NADPH oxidase inhibitor apocynin by inhibiting free radical generation and increasing antioxidant defense exerts protective effects on testicular tissues against I/R. The protection with apocynin was more pronounced with high dose. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Spermatic cord torsion; Testis; Reperfusion injury; Apocynin; OXIDATIVE STRESS; NADPH OXIDASE; FREE-RADICALS; DAMAGE; GLUTATHIONE; MECHANISMS; HYPERTENSION; INFLAMMATION; SUPEROXIDE; EXPRESSION